Resilience among women religious: Concept, characteristics, risk and protective factors, and process implications for enhancement - Olapureckal, Baby Rani Gervadis (Animo Repository, 2007)
The study explored resilience among religious women in India: concept, risk and protective factors, process, characteristics and implications for intervention. The participants of the study were nine high resilient women religious, selected from a pool of 300 women religious from the Sisters of the Adoration of the Blessed Sacrament. The Religious Resilience Inventory and self assessment report were used for selection. Consensual Qualitative Research was employed. In-depth interviews were conducted for data collection. Descriptive statistics and content analysis were utilized in data analysis. Results indicate that women religious consider resilience as ability, a process and a grace from God. Risk and protective factors are related to community, family, apostolate, sickness and climate. The process of resilience consists of disruption, reintegration and homeostasis. Some characteristics of resilient women religious are strong faith, optimism, and high self esteem. On the basis of the findings and the participants’ suggestions, a Resilience Training Program was designed and pilot tested to a group (N= 10) of Indian women religious in Manila. It was found to enhance resilience.